Pemanfaatan Media Sosial Untuk Meningkatkan Kemampuan Bahasa Inggris Mahasiswa Di STAI Tapanuli Padangsidimpuan - Marwah, Marwah (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the utilization of social media in improving the English language proficiency of students at STAI Tapanuli Padangsidimpuan. The research employed a descriptive qualitative method with a field research approach conducted from January to May 2025. Data were collected through observation, interviews, and documentation involving students of the Islamic Education Study Program who actively used social media as a learning tool for English. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that students actively utilize various platforms such as YouTube, Instagram, TikTok, WhatsApp, and Facebook for English learning. YouTube serves as the main platform for studying grammar, listening, and pronunciation; Instagram is used for visual microlearning; TikTok functions as an edutainment medium; WhatsApp facilitates collaboration and discussion; while Facebook acts as a global learning community. The use of social media has a significant positive impact on improving students listening, vocabulary, speaking, writing, and reading skills, as well as their learning motivation. Supporting factors include technological accessibility, the availability of educational content, and students familiarity with digital platforms. Meanwhile, inhibiting factors include distractions, information overload, lack of feedback, limited internet access, exposure to inappropriate content, and the risk of addiction that may affect students health and learning concentration